The Importance of Strong Organizational Culture in Nurse Performance Over Regional Government Hospital Jakarta - Verly Vernadeth; Rina Anindita; Mus Aida (Penerbit Kemala Indonesia, 2020)
Human resources are important thing for hospitals. Therefore, human resources must have a good quality of performance to achieve the vision and mission of the hospital. Thus, this study aimed to analyze the influence of organizational culture on the performance of nurses with work discipline as an intervening variable in RSUD Pesanggrahan. This research is a quantitative study with a causal research design with 44 respondents conducted on May 2019 to August 2019. The determination of the samples number using census method. Here, research variables are performed as a dependent variable, Organizational Culture as an independent variable, and Work Discipline as an intervening variable. The collecting data in this study, we use a questionnaire with technical research instruments with questionnaire in 4 levels Likert scale. Here, we analyze the data using path analysis. The results showed that the relationship between organizational culture and performance was not significant while organizational culture has a positive and significant influence on work discipline also organizational culture has an influence on the performance of nurses with work discipline in intervening variable. The managerial implications can be applied to improve work performance to increase work discipline and stronger organizational culture.